2014
DOI: 10.2166/wst.2014.315
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of iron oxide nanoparticles coated with chitosan for removal of Cd(II) and Cr(VI) from aqueous solution

Abstract: This study investigated the applicability of magnetite Fe(3)O(4) nanoparticles coated with chitosan (CMNs) for the removal of some toxic heavy metals from simulated wastewater. Magnetic nanomaterials were synthesized using the co-precipitation method and characterized by transmission electron microscope, scanning electron microscope, X-ray diffraction, and Fourier transformer infrared spectroscopy. The magnetic properties of the prepared magnetic nanoparticles were determined by a vibrating-sample magnetometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…This creates electrostatic attraction between the hydronium ions and chromium ions resulting in better adsorption. However, chromium ions also compete for the protons at the lower pH 44,45Figure 12Optimization of pH for chromium removal.…”
Section: Resultsmentioning
confidence: 99%
“…This creates electrostatic attraction between the hydronium ions and chromium ions resulting in better adsorption. However, chromium ions also compete for the protons at the lower pH 44,45Figure 12Optimization of pH for chromium removal.…”
Section: Resultsmentioning
confidence: 99%
“…Even the nanoparticles also adsorbs chromium; thus, chitosan-coated nanoparticles showed greater efficiency than the control. Even the applied acidic pH has its role in adsorption and removal of heavy metal from wastewater (Alzaidi et al 2016;Shalaby et al 2014).…”
Section: Chromium Metal Adsorption Studiesmentioning
confidence: 99%
“…9a-c). This suggested that the binding sites on the adsorbent were heterogeneous and multilayer adsorption of chromium could occur (Jiang et al 2013;Shalaby et al 2014).…”
Section: Chromium Metal Adsorption Studiesmentioning
confidence: 99%
“…In addition, the surface charge of nanoadsorbents depends on the pH of solvent. The surface charge becomes neutral at pH 5.8 for iron oxide; further lowering the pH will render the adsorbent surface rich in positive charges and Cr(VI), resulting in better adsorption [37,38]. On the other hand, non-treated composite membrane and bare PVDF exhibited much lower removal efficiencies than that of pretreated Chi@Fe 2 O 3 -PVDF (Figure 5a).…”
Section: Effect Of Solution Phmentioning
confidence: 99%